Effectiveness of community-based Baduanjin exercise intervention for older adults with varying frailty status: a randomized controlled trial. - Tou, Nien Xiang; Goh, Siew Fong; Harding, Susana; Tsao, Mary Ann; Ng, Tze Pin; Wee, Shiou-Liang (European Review of Aging & Physical Activity)
Background: Due to poorer exercise tolerance, it may be challenging for frail older adults to engage in moderate- or vigorous-intensity exercise. While low-intensity exercise interventions may be more feasible, its effectiveness for such population group remains unclear. We examined the effectiveness and implementation of community-based Baduanjin Qigong, a low-intensity exercise program in older adults with varying frailty status. Methods: A two-arm, multicenter assessor-blind parallel group randomized controlled trial was conducted at three local senior activity centers. Fifty-six community-dwelling older adults with low handgrip strength were randomly allocated to either the intervention (IG) or wait-list control (CG) group. The IG underwent a supervised 16-week Baduanjin exercise program at a frequency of 2–3 × 60 min sessions/week. The CG was instructed to maintain their usual activity and received a monthly health education talk. The primary outcome measures were knee extension strength, vital exhaustion, and fear of falling. Secondary outcome measures include physiological falls risk, handgrip strength, gait speed, timed up and go test, 30-second sit-to-stand, quality of life, depression, and frailty. All outcome measures were assessed at baseline and 4-month follow-up. Results: Overall, there were no statistically significant differences in all outcome measures between CG and IG at 4-month follow-up. However, in exploratory compliance analysis, a statistically significant group x time interaction was found for vital exhaustion (B = -3.65, 95% CI [-7.13, -0.16], p =.047) among participants with at least 75% attendance. In post-hoc within-group comparisons, IG showed improved vital exhaustion by 4.31 points (95% CI [1.41, 7.20], d = 0.60). The average participant attendance rate was 81.3%. No major adverse events occurred, and all participants reported positive experiences with the exercise intervention. Conclusions: Our study demonstrated that Baduanjin is a safe, feasible, and acceptable exercise program that can be successfully implemented in community settings for older adults with varying frailty status. With good adherence, Baduanjin exercise could potentially be effective in alleviating vital exhaustion. However, the effectiveness of Baduanjin on physical performance, psychological measures and frailty in community-dwelling older adults remains equivocal. Trial registration: ClinicalTrials.gov NCT04549103. Registered September 16, 2020.